The Impact of Perceived Usefulness, Ease of Use, and Digital Payment Integration on FinTech Adoption: An Empirical Study in Pakistan - Kehkashan; Qamar, Sunain; Ahsan; Ullah, Asif (Journal of Peace, Development and Communication, 2024)
The integration of technology, particularly in Financial Technology (Fintech), has reshaped the landscape of financial services globally. Understanding the factors driving Fintech adoption is crucial for policymakers, regulators, and stakeholders. This empirical study investigates the impact of perceived usefulness, ease of use, and digital payment integration on Fintech adoption in Pakistan, utilizing the (TAM) framework. Through a thorough literature review, theoretical framework development, and methodological approach employing exploratory factor analysis and regression analysis, this study explores the intricate dynamics of Fintech adoption. Results reveal significant relationships between perceived usefulness, ease of use, digital payments, and Fintech adoption. The findings contribute to a deeper understanding of Fintech adoption dynamics in emerging markets, offering insights for policymakers and stakeholders to foster financial inclusion and innovation. Future research directions include examining disparities in Fintech adoption across income groups to inform tailored strategies for inclusive Fintech adoption.